Experience of Remifentanil in Extremely Low-birth-weight Babies Undergoing Laparotomy - Maria Sammartino; Rossella Garra; Fabio Sbaraglia; Mariella De Riso; Nicola Continolo; Patrizia Papacci (Elsevier, 2011)
Premature babies experience pain and require adequate analgesia for any painful procedure. Fentanyl and morphine resulted in safe and effective anesthesia in the past; however, their pharmacokinetics may be impaired in preterm babies with multiorgan failure. Remifentanil, despite the absence of available pharmacokinetic data in preterm infants and few reports in newborns, demonstrated its advantages in children undergoing either major surgery or minor painful procedures and has been shown to be useful even in neonates, because its elimination is independent of organ function. We report two cases of babies born at 26 weeks' and 27 weeks' gestation, weighing 580 g and 400 g, respectively, undergoing laparotomy for necrotizing enterocolitis. Both received midazolam bolus and remifentanil infusion at high doses. This technique seems to be an advantageous alternative even in extremely low-birth-weight prematures. Furthermore, it becomes a technique of choice in these babies because the available ventilators are often not equipped with halogenated vaporizers. Particularly in intensive care, where there are no scavenger systems, it could allow to operate without moving out the preterm babies and avoiding stress and hypothermia.